PERBEDAAN HASIL BELAJAR SISWA MELALUI PENERAPAN STRATEGI PERTUKARAN KELOMPOK DENGAN KELOMPOK DENGAN STRATEGI EKSPOSITORI PADA MATA PELAJARAN EKONOMI KELAS X SMAN 2 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Gustia Ningsih, Sherly; Armiati, M.Pd, Armiati, M.Pd; Areva, S.Pd, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTthis research based by low result of economy learner. That cause by some factors, the factors such as method which teacher still used teacher center, the studeSns less involve in teaching learning and value which used result of value not process of value. The goal of this research is for looking different result if learner student used strategy group to group echange which strategy ekspositori at SMA N 2 Pancung Soal . Kind of this result is experimental of research and interpretation sample technique that used is purposive sampling. Population of all the student grade X SMA N 2 Pancung Soal, was chosen as the experimental class is the class X3 and X4 Control class. Analysis data of technique which use by t experimental because of data normal distribution and group of data has variation that homogen. The result of experiment showed average result of learning experiment class is 82 which standar deviassi is 7.91 while the average class control is 77.2 which standart deviasi 8.28. Based analysis data which got, thitung (2,330) so that the found is H0 regected an H1 accepted. So that conclude there are different the result student used strategy group to group echange with strategy ekspositori..